Esophageal tissue engineering. (March 2014) - Luc, Guillaume; Durand, Marlène; Collet, Denis; Guillemot, Fabien; Bordenave, Laurence
Abstract : Esophageal tissue engineering is still in an early state, and ideal methods have not been developed. Since the beginning of the 20th century, advances have been made in the materials that can be used to produce an esophageal substitute. Three approaches to scaffold-based tissue engineering have yielded good results. The first development concerned non-absorbable constructs based on silicone and collagen. The need to remove the silicone tube is the main disadvantage of this material. Polymeric absorbable scaffolds have been used since the 1990s. The main polymeric material used is poly (glycolic) acid combined with collagen. The problem of stenosis remains prevalent in most studies using an absorbable construct. Finally, decellularized scaffolds have been used since 2000. The promises of this new approach are unfulfilled. Indeed, stenosis occurs when the esophageal defect is circumferential regardless of the scaffold materials. Cell supplementation can decrease the rate of stenosis, but the type(s) of cells and their roles have not been defined. Finally, esophageal tissue engineering cannot provide a functional esophageal substitute, and further development is necessary prior to conducting human clinical studies.